Suggesting Multipath Routing and Dividing the Zone to Process Communication Failure in Ad Hoc Networks - Jarah, Nada Badr (Iraqi Journal of Science, 2021)
Ad hoc networks are characterized by ease of setup, low costs, and frequent use in the corporate world. They ensure safety to the user and maintain the confidentiality of the information circulated. They also allow the user to address the cases of communication failure in areas subject to destruction of communication infrastructure. The proposed protocols in the ad hoc networks often build only one path to achieve communication between the nodes, due to the restrictions of battery run out and the movement of the nodes. This connection is often subject to a failure within a certain range. Thus, multiple alternate paths in ad hoc networks use a solution to failing node communications. In addition, when looking at the situation where interference is widespread, each path is preferably somewhat distant from the others. In this paper, we present a simple processing by building multipath routing that do not overlap at the level of an ad hoc network zone, which is achieved through dividing the zone. The evaluation performed by using Network Simulator (ns-allinone-3.20) showed that the proposed ad hoc network connection is more efficient than the connection with the traditional methods of constructing multipath routings.